Vegetation and ecoregion analysis at Sipirok Botanic Gardens, South Tapanuli, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Siregar M, Purnomo DW, Siregar HM, Witono JR. 2020. Vegetation and ecoregion analysis at Sipirok Botanic Gardens, South Tapanuli, North Sumatra, Indonesia. Biodiversitas 21: 2526-2535. Botanic Gardens is an ex-situ plant conservation area. Enrichment of plant collections of Botanic Gardens in Indonesia is based on ecoregion types. To find out the type of ecoregion, the existing vegetation, main native species should be known. The research aimed to analyze the existing vegetation and ecoregion type at Sipirok Botanic Gardens. Existing vegetation has been carried out using a separate plot method 20x20 m which is placed on purposively in nine locations considered to have different vegetation types, namely remnant forest, young secondary forests and shrubs, rubber plantation, and grasslands. Around 66 species belonged to 45 genera and 27 families were found in vascular plants (dbh ? 10 cm). There were 66 species of sapling belonged to 54 genera and 35 families, and 110 seedlings belonged to 87 genera and 50 families. The tree species that have the highest Importance Value Index are Ficus sumatrana (PU-1), Myristica fatua (PU-3), Hevea brasiliensis (PU-4 and PU-7), Artocarpus elasticus (PU-8), and Knema cinerea (PU-9). No trees were found in young secondary forest/shrub plots and grasslands. Unlike the species dominance index, the species diversity index and species equitability index are higher in natural forest plots. Beta diversity based on Jaccard similarity index and Whittaker's index shows a relatively different species composition among plots. Cluster analysis shows the tendency of grouping in 2 types of communities, namely: a) remnant forest communities, and b) secondary communities. The natural forest community is further divided into two communities consisting of remnant forest tree species and industrial/plantation plant species also secondary tree species. Secondary communities are also further divided into secondary forest communities and grasslands. Based on ecoregion analysis using previous publications, altitude, and diversity of plant species in the study site, Sipirok Botanic Gardens is a transitional zone of the Sumatran lowland rainforest and mountain rainforest.
Keywords: Ecoregion, North Sumatra, Sipirok Botanic Gardens, vegetation analysis